2012
DOI: 10.1007/s10561-012-9292-6
|View full text |Cite
|
Sign up to set email alerts
|

Tissue cryobanking for conservation programs: effect of tissue type and storage time after death

Abstract: In this study, we investigated the temporal post-mortem limits, within which there will be guarantees of obtaining living cells from several tissues of sheep and cattle and the effect of vitrification on the ability of cells from tissue stored at different times. Muscle tissue and auricular cartilage were stored at 4°C for 5, 48, 72, 96 and 216 h post-mortem (hpm). Tissue samples were sorted into two groups: one group was in vitro cultured immediately after storage and the other was vitrified after storage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In a study by Caamaño et al (2008), vitrification showed lower efficiency compared to SF and noncryopreserved tissues derived from brown bears ( Ursus arctos ), suggesting that high concentrations of cryoprotectants affect the quality of vitrified tissues. Additionally, other factors may influence the efficiency of the SSV, such as the use of a pre‐equilibration solution/step, tissue type (Caputcu et al, 2013), tissue thickness (Carvalho et al, 2013), warming and reanimation conditions (Lima et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Caamaño et al (2008), vitrification showed lower efficiency compared to SF and noncryopreserved tissues derived from brown bears ( Ursus arctos ), suggesting that high concentrations of cryoprotectants affect the quality of vitrified tissues. Additionally, other factors may influence the efficiency of the SSV, such as the use of a pre‐equilibration solution/step, tissue type (Caputcu et al, 2013), tissue thickness (Carvalho et al, 2013), warming and reanimation conditions (Lima et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in regions of difficult access, a greater number of individuals can be collected, without restricting the age and gender, thus allowing an unlimited number of samples and the extrapolation of these cell characteristics for the entire population (León-Quinto et al 2009). Therefore, somatic tissue samples can contribute to preservation programs (Caputcu et al 2013;Silvestre et al 2004). These skin cryobanks permit the maintenance of a maximal representation of biodiversity population, being an important tool in wildlife preservation programs (León-Quinto et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In general, slow freezing uses low concentrations of cryoprotectants and is done through gradual temperature reduction in a controlled manner. Although not performed in wild felids, vitrification has also been a prominent method in tissue cryopreservation and has been used in somatic tissues of some mammals (Borges et al, ; Caputcu, Akkoc, Cetinkaya, & Arat, ). This technique is performed through rapid temperature reduction and with high concentrations of cryoprotectants.…”
Section: Cryopreservation Techniques Of Somatic Cells and Tissuesmentioning
confidence: 99%